American Heart Association, 2009 Scientific Sessions - Alexander, Walter (MediMedia USA, Inc., 2010)
The American Heart Association (AHA) 2009 Scientific Sessions hosted nearly 22,000 cardiologists, other health professionals, and industry exhibitors in Orlando, Florida, from November 14 to 18, 2009. This overview covers the late-breaking clinical trial presentation of ARBITER 6-HALTS, a lipid treatment strategy study that attracted more attention and controversy than others; a clinical trial of angiotensin-receptor blockers in heart failure; and two other sessions that examined the effects of lipids on both cardiovascular disease and cancer.